P8. The in vitro comparison of gold nanoparticles in different cell lines. (September 2016) - Engelbrecht, M.; De Kock, M.; Slabbert, J.P.
Abstract : Introduction: Gold nanoparticles (AuNPs) have been recognized as effective radiosensitizers of low energy (e.g. 200–500 kV) X-rays, leading to the emission of Auger electrons that cause highly localized ionizing damage to cells. The aim of this study was to determine possible toxicity caused by AuNPs and to establish whether the AuNPs interacts with MV X-rays. Materials and methods: The interaction between the 5 and 10 nm AuNPs with 6 MV X-rays were carried out in different cell lines, namely CHO-K1, BEnd5, MCF-7 and MCF-10A. The X-rays is a low linear energy transfer (LET) radiation type, which was scattered by using a Shonka chamber to obtain lower energies X-rays to interact with the AuNPs. The cells were incubated with 50 μg/ml of the respective AuNPs for 4 h and given a 2 Gy dose. The media was replaced and the cells were incubated for 24 h in the presence of cytochalasin B, then fixed and stained with acridine orange. Results: In some of the cell types used in this study, higher MNi frequencies were induced by a combination treatment of radiation and AuNPs compared to the additive sum noted in samples exposed to AuNPs and radiation separately. The AuNPs alone reduced the growth rate of all types between 29% and 33%. Conclusion: Interactions between the AuNPs and scattered 6 MV X-rays were noted for CHO-K1 and MCF-7 cells, but not for other cell types used in the study. The cellular uptake for AuNPs needs to be quantified to explain the results.